New combinations in Odontoglossum (Orchidaceae: Oncidiinae) and a solution to a taxonomic conundrum - Dalström, Stig (2012)
The diminutively flowered Oncidium koechliniana demonstrates a unique combination of features that justifies a transfer of it and all here accepted species in closely related genera Cochlioda and Solenidiopsis to Odontoglossum, which is executed here. Distinguishing features to separate Odontoglossum from Oncidium are based on geographic distribution, and flower morphology, which is demonstrated with illustrations.